Errors in estimating usual sodium intake by the Kawasaki formula alter its relationship with mortality: implications for public health. (22nd June 2018) - He, Feng J; Campbell, Norm R C; Ma, Yuan; MacGregor, Graham A; Cogswell, Mary E; Cook, Nancy R
Abstract: Background: Several cohort studies with inaccurate estimates of sodium reported a J-shaped relationship with mortality. We compared various estimated sodium intakes with that measured by the gold-standard method of multiple non-consecutive 24-h urine collections and assessed their relationship with mortality. Methods: We analysed the Trials of Hypertension Prevention follow-up data. Sodium intake was assessed in four ways: (i) average measured (gold standard): mean of three to seven 24-h urinary sodium measurements during the trial periods; (ii) average estimated: mean of three to seven estimated 24-h urinary sodium excretions from sodium concentration of 24-h urine using the Kawasaki formula; (iii) first measured: 24-h urinary sodium measured at the beginning of each trial; (iv) first estimated: 24-h urinary sodium estimated from sodium concentration of the first 24-h urine using the Kawasaki formula. We included 2974 individuals aged 30–54 years with pre-hypertension, not assigned to sodium intervention. Results: During a median follow-up of 24 years, 272 deaths occurred. The average sodium intake measured by the gold-standard method was 3769 ± 1282 mg/d. The average estimated sodium over-estimated the intake by 1297 mg/d (95% confidence interval: 1267–1326). The average estimated value was systematically biased with over-estimation at lower levels and under-estimation at higher levels. The average measured sodium showed a linear relationship with mortality. The average estimated sodium appeared to show a J-shaped relationship with mortality. The first measured and the first estimated sodium both flattened the relationship. Conclusions: Accurately measured sodium intake showed a linear relationship with mortality. Inaccurately estimated sodium changed the relationship and could explain much of the paradoxical J-shaped findings reported in some cohort studies.